PERSEPSI MAHASISWA BIDIKMISI UNIVERSITAS DIPONEGORO TERHADAP HARAPAN MASA DEPANNYA - Eva Nurlaily Rohmah; Warsito .; Turtiantoro . (Journal of Politic and Government Studies, 2015)
ABSTRACTThe Poverty is still a fundamental problem that must be faced by the Indonesiangovernment. One of the effects of poverty is the low level of public education. Therefore,to break the vicious circle of poverty, the government develop policies of education byproviding scholarships to students who have good academic potential and theeconomically disadvantaged, the program is a program Bidikmisi (Beasiswa PendidikanBagi Mahasiswa Berprestasi). The Bidikmisi scholarships as government policies that canmotivate people to compete in a weak economy seize the opportunity to continue theireducation at the famous State University in hopes of changing the future. It raises thepublic perception of bidikmisi education policy in realizing his future hopes. Therefore,the problem in this research is "How the perception of Bidikmisi students at DiponegoroUniversity to their future expectation??". This research purposes to describe theperception of Bidikmisi Students at Diponegoro University to their future expectation.While, the type of research used descriptive type. The primary data source in this researchproduced by interviews conducted by researchers with the informant using purosivesampling techniques. For secondary data generated in this research of documents,archives and internet. Analysis technique using data analysis with data reduction, datapresentation and draw conclusions or verification. From the research, it is known thatbidikmisi Scholarship Assistance Program has provided opportunities for students fromeconomically disadvantaged families. The program raises the hope of Students Bidikmisifor the future of the family, expectations of academic achievement, dedication to thenation and the application of science. With a professional background of parents arediverse and different student residence does not provide that much difference to thestudents in giving perception because they have in common is the lack of economicbackground..Keyword: Bidikmisi Scholarship, Poverty, Diponegoro University